2009
DOI: 10.1126/science.1174290
|View full text |Cite|
|
Sign up to set email alerts
|

Coupling Mechanics to Charge Transport in Carbon Nanotube Mechanical Resonators

Abstract: Nanoelectromechanical resonators have potential applications in sensing, cooling, and mechanical signal processing. An important parameter in these systems is the strength of coupling the resonator motion to charge transport through the device. We investigated the mechanical oscillations of a suspended single-walled carbon nanotube that also acts as a single-electron transistor. The coupling of the mechanical and the charge degrees of freedom is strikingly strong as well as widely tunable (the associated dampi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
432
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(455 citation statements)
references
References 28 publications
19
432
1
3
Order By: Relevance
“…We grow the nanotube by chemical vapour deposition in the last fabrication step in order to avoid contamination 9 . All measurements are performed at 65 K to avoid Coulomb blockade 2,3 . We have studied five nanotube devices in total.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We grow the nanotube by chemical vapour deposition in the last fabrication step in order to avoid contamination 9 . All measurements are performed at 65 K to avoid Coulomb blockade 2,3 . We have studied five nanotube devices in total.…”
Section: Resultsmentioning
confidence: 99%
“…Its crystallinity confers excellent mechanical properties to nanotube-based resonators [1][2][3][4][5][6] , such as high resonant frequencies 7,8 and low dissipation at low temperature 9,10 . As a result, these resonators are well suited for ultra-sensitive detection of mass 11,12 , charge 2,3 and force 13 . A nanotube has also much in common with a polymer as both can bend by a large amount.…”
mentioning
confidence: 99%
“…Last year, for example, three groups showed that it was possible to measure the change that occurred in the resonant frequency of a suspended nanotube when a single atom landed on it, thus forming the basis of ultrasensitive mass sensors [7][8][9] . Now Adrian Bachtold and co-workers 10 and, independently, Gary Steele and colleagues 11 have explored the coupling between the mechanical motion of a nanotube and the flow of electrons through the nanotube, and shown that it is possible to detect frequency changes caused by the addition of just one electron to the nanotube. Both groups also find that the coupling is strong enough to drive nonlinear oscillations of the nanotube.…”
Section: Editorialmentioning
confidence: 99%
“…Such a quantum dot may be realized on a suspended CNT using electronic back gates to confine an electron in a specific section of the nanotube. 6,[9][10][11][12][15][16][17]20 The vibrations of the CNT can be strongly coupled to the charge degree of freedom of the electron and thus have a great influence on its conductive properties. 12,20,21 Additionally, a back gate can be used to apply an ac voltage, thus modulating the dot energy level.…”
Section: Modelmentioning
confidence: 99%
“…13,14 Nanoelectromechanics is a growing field of research with various experiments investigating the interplay between the mechanical and the quantized electronic degree of freedom in suspended CNTs. 12,[15][16][17] A general feature of interacting systems composed of electrons and quantized mechanical vibrations ("vibrons") is the suppression of conductance, in certain parameter regimes, for strong coupling between the two degrees of freedom. This effect, commonly referred to as Franck-Condon blockade, 18 results from the atomic constituents of the system accommodating for the presence of a number of electrons by means of displacement, thus forming composite electron-vibron particles termed polarons.…”
Section: Introductionmentioning
confidence: 99%